2007
DOI: 10.1007/s10209-007-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterising user capabilities to support inclusive design evaluation

Abstract: Designers require knowledge and data about users to effectively evaluate product accessibility during the early stages of design. This paper addresses this problem by setting out the sensory, cognitive and motor dimensions of user capability that are important for product interaction. The relationship between user capability and product demand is used as the underlying conceptual model for product design evaluations and for estimating the number of people potentially excluded from using a given product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 30 publications
0
56
0
4
Order By: Relevance
“…However, the focus of rehabilitation engineering is much broader than just computer use. Rehabilitation engineering focuses on developing engineering models of human performance (Kondraske 1988a, Kondraske 1995, Persad et al 2007) and often measures that performance on task batteries that include many non-computer-related tasks (Kondraske 1990a, Kondraske 1990b, Smith and Kondraske 1987. Also, accommodations in rehabilitation engineering are often custom add-on devices or machines, giving rehabilitation engineering much in common with assistive technology.…”
Section: Rehabilitation Engineeringmentioning
confidence: 99%
“…However, the focus of rehabilitation engineering is much broader than just computer use. Rehabilitation engineering focuses on developing engineering models of human performance (Kondraske 1988a, Kondraske 1995, Persad et al 2007) and often measures that performance on task batteries that include many non-computer-related tasks (Kondraske 1990a, Kondraske 1990b, Smith and Kondraske 1987. Also, accommodations in rehabilitation engineering are often custom add-on devices or machines, giving rehabilitation engineering much in common with assistive technology.…”
Section: Rehabilitation Engineeringmentioning
confidence: 99%
“…[5] That is, for some older adults, more interaction steps and thinking time for small screen interaction were needed, especially for diverse characteristics of the older population. Altogether, results of this study and the previous works suggested that the elderly tend to require more interaction steps than the other age groups.…”
Section: Resultsmentioning
confidence: 99%
“…This can be for example the processing of visual or auditory senses (Esgate et al, 2005) when working with an information system. Figure 2 depicts a simplified model of how the human brain handles cognitive processing (Persad et al, 2007).…”
Section: Insights Of Neuroscience On Cognitive Processingmentioning
confidence: 99%